Activation of Secondary Metabolism in Red Soil-Derived Streptomycetes via Co-Culture with Mycolic Acid-Containing Bacteria - Kairui Wang (MDPI AG, 2021)
Our previous research has demonstrated a promising capacity of streptomycetes isolated from red soils to produce novel secondary metabolites, most of which, however, remain to be explored. Co-culturing with mycolic acid-containing bacteria (MACB) has been used successfully in activating the secondary metabolism in Streptomyces. Here, we co-cultured 44 strains of red soil-derived streptomycetes with four MACB of different species in a pairwise manner and analyzed the secondary metabolites. The results revealed that each of the MACB strains induced changes in the metabolite profiles of 35–40 streptomycetes tested, of which 12–14 streptomycetes produced “new” metabolites that were not detected in the pure cultures. Moreover, some of the co-cultures showed additional or enhanced antimicrobial activity compared to the pure cultures, indicating that co-culture may activate the production of bioactive compounds. From the co-culture-induced metabolites, we identified 49 putative new compounds. Taking the co-culture of Streptomyces sp. FXJ1.264 and Mycobacterium sp. HX09-1 as a case, we further explored the underlying mechanism of co-culture activation and found that it most likely relied on direct physical contact between the two living bacteria. Overall, our results verify co-culture with MACB as an effective approach to discover novel natural products from red soil-derived streptomycetes.